One‐step hydrothermal synthesis of double core‐shell oxygen‐incorporated molybdenum disulfide and its tribological properties. (23rd February 2021) - Chen, Ying; Li, Yuan; Liang, Yuning; Chen, Xuesong; Cui, Jinjin
Abstract: Using a simple one‐step hydrothermal method, benzyl triethylammonium chloride was used to assist the synthesis of double core‐shell oxygen‐incorporated molybdenum disulfide (DB‐O‐MoS2 ), and its friction and wear properties were measured on the MRS‐10A four‐ball testing machine. They were characterised by X‐ray diffraction, scanning electron microscope, transmission electron microscope, thermogravimetry, Brunner−Emmet−Teller and Fourier transform infrared spectroscope. Friction and wear properties of DB‐O‐MoS2 were measured at different concentrations. The results showed that the tribological properties of SN 5W‐40 base oil have been improved by adding the DB‐O‐MoS2 as lubricant additives. The possibility of DB‐O‐MoS2 mechanisms by which the nanolubricants improved the tribological properties were put forward. Therefore, research on DB‐O‐MoS2 is beneficial to the development of new engine lubricant additives.